Decision-model estimation of the age-specific disability weight for schistosomiasis japonica: a systematic review of the literature. - Julia L Finkelstein; Mark D Schleinitz; Hélène Carabin; Stephen T McGarvey (Public Library of Science (PLoS), 2008)
Schistosomiasis is among the most prevalent parasitic infections worldwide. However, current Global Burden of Disease (GBD) disability-adjusted life year estimates indicate that its population-level impact is negligible. Recent studies suggest that GBD methodologies may significantly underestimate the burden of parasitic diseases, including schistosomiasis. Furthermore, strain-specific disability weights have not been established for schistosomiasis, and the magnitude of human disease burden due to Schistosoma japonicum remains controversial. We used a decision model to quantify an alternative disability weight estimate of the burden of human disease due to S. japonicum. We reviewed S. japonicum morbidity data, and constructed decision trees for all infected persons and two age-specific strata, <15 years (y) and > or =15 y. We conducted stochastic and probabilistic sensitivity analyses for each model. Infection with S. japonicum was associated with an average disability weight of 0.132, with age-specific disability weights of 0.098 (<15 y) and 0.186 (> or =15 y). Re-estimated disability weights were seven to 46 times greater than current GBD measures; no simulations produced disability weight estimates lower than 0.009. Nutritional morbidities had the greatest contribution to the S. japonicum disability weight in the <15 y model, whereas major organ pathologies were the most critical variables in the older age group. GBD disability weights for schistosomiasis urgently need to be revised, and species-specific disability weights should be established. Even a marginal increase in current estimates would result in a substantial rise in the estimated global burden of schistosomiasis, and have considerable implications for public health prioritization and resource allocation for schistosomiasis research, monitoring, and control.